Exploring Challenges and Solutions in Tourism Village Management in the Manggarai Region, NTT: Mengeksplorasi Tantangan dan Solusi dalam Pengelolaan Desa Wisata di Wilayah Manggarai, NTT - Ndiung, Sabina; Sutam, Inosensius; Menggo, Sebastianus (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
Objects in tourism villages are valuable resources which government villages can employ to improve the prosperity of rural communities throughout Indonesia. Using these assets is an essential component of managing a tourist destination. The level of service provided to tourists is determined by how successfully the management performs their responsibilities. This Community Service explores the challenges that arise when developing eight tourist villages in the Manggarai district of West Flores, Indonesia. This Community Service is expected to address numerous problems in the management of eight tourist villages by involving 93 tourism stakeholders. This Community Service activity was carried out in eight villages during two months (November – December 2023). Data collection in this service through questionnaires, observations and interviews, then data was analyzed descriptive-quantitatively. The results show that eight villages have a number of obstacles, such as unavailability of tourist information centers in tourist villages (86%), English language communication (82.8%), rabid animals or other infectious agents at tourist locations (82.8%), infrastructure (78 .5%), environmental sustainability (77.4%), followed by hygiene and health issues (71%). The West Flores tourism community has a lot of potential, but it will only come true if it has been prepared for and the right steps are taken immediately.